Piero della Francesca : artist & man - James R.Banker (Oxford University Press, 2014)
"Largely neglected for the four centuries after his death, Piero della Francesca is now seen to embody the fullest expression of the Renaissance perspective painter, raising him to an artistic stature comparable with that of Leonardo da Vinci and Michelangelo. But who was Piero, and how did he become the person and artist that he was? Until now...these questions have remained largely unanswered. Piero della Francesca: Artist and Man puts that situation right, integrating the story of Piero's artistic and mathematical achievements with the full chronicle of his life for the first time. Fortified by his discovery of over one hundred previously unknown documents, James R. Banker at last brings this fascinating Renaissance enigma to life."--Front inside flap of dust jacket.